Fuel cell catalyst, preparation method and application

By using a catalyst composed of nitrogen-doped carbon nanocage and cobalt nanoparticles in the fuel cell catalyst, the problems of high cost and low activity of fuel cell catalysts are solved, efficient catalytic activity and low cost production are achieved, and fuel cells are significantly improved performance.

CN119275299AActive Publication Date: 2025-01-07CHERY AUTOMOBILE CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411406451.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The high cost and low catalytic activity of existing fuel cell catalysts, especially the slow kinetic process of cathode oxygen reduction reaction, has led to limited development of fuel cells.

Method used

Using a fuel cell catalyst preparation method, by mixing cobalt nitrate, zinc nitrate and 2-methylimidazole, a catalyst composed of nitrogen-doped carbon nanocage and cobalt nanoparticles is formed. The carbon nanotubes are grown in nitrogen-doped carbon nanocage. On the surface, cobalt nanoparticles are coated inside the carbon nanotubes and cages, using nitrogen doping and Mott-Schauttky effect to improve catalytic activity, and forming a three-dimensional network through carbon nanotubes to improve conductivity.

Benefits of technology

It has achieved the reduction of production costs and improved catalytic activity, avoided the problem of poor contact between active metal nanoparticles and carbon materials, improved the specific surface area and graphitization degree of the catalyst, and significantly improved the catalytic activity and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275299A_ABST
    Figure CN119275299A_ABST
Patent Text Reader

Abstract

The invention discloses a fuel cell catalyst, a preparation method and application, and belongs to the technical field of batteries. The catalyst prepared in the invention is composed of a nitrogen-doped carbon nanocage, cobalt nanoparticles and carbon nanotubes, the carbon nanotubes grow on the surface of the nitrogen-doped carbon nanocage, and the cobalt nanoparticles are coated in the carbon nanotubes and the carbon nanocage. The doping of the nitrogen element increases the catalytic active sites of the catalyst material and improves the catalytic activity; the Mott-Schottky effect between the cobalt nanoparticles and the carbon material enables electrons to be transferred from the metal material to the carbon material, the non-uniform electron distribution enables the catalytic activity of the catalyst material to be further improved, and the cobalt nanoparticles are wrapped in the carbon material, so that the problem of poor contact between the active metal nanoparticles and the carbon material is avoided. In addition, the materials adopted by the catalyst are low in cost and easy to obtain, and the preparation process is simple, so that the catalyst prepared by the invention not only has lower production cost, but also has higher catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a fuel cell catalyst, a preparation method and an application thereof. Background Art

[0002] Oxygen reduction reaction (ORR) is the most critical technology in fuel cells, but the cathode oxygen reduction reaction kinetics are very slow, so a suitable catalyst is needed to promote the reaction. The high cost and limited resources of Pt-based catalysts have greatly restricted the development of fuel cells. Therefore, the development of efficient, long-life, non-Pt-based fuel cell catalysts is the basis for reducing the cost of fuel cells and promoting the large-scale application of fuel cells.

[0003] In the related art, either the nano-carbon carrier is modified by heteroatom doping or graphene composite carbon material is introduced. However, the heteroatom doping of the nano-carbon carrier is prone to the problem of poor contact between the carbon material and the active metal nanoparticles, resulting in low catalytic activity of the fuel cell catalyst. The introduction of graphene composite carbon material will result in high production costs. Therefore, it is necessary to provide a fuel cell catalyst that can reduce production costs and improve catalytic activity. Summary of the invention

[0004] The present application provides a fuel cell catalyst, preparation method and application, which can reduce production costs and improve catalytic activity. The technical solution is as follows:

[0005] In one aspect, a method for preparing a fuel cell catalyst is provided, the method comprising:

[0006] respectively preparing a methanol solution of cobalt nitrate, a methanol solution of zinc nitrate and a methanol solution of 2-methylimidazole;

[0007] The cobalt nitrate methanol solution, the zinc nitrate methanol solution and the 2-methylimidazole methanol solution are mixed, and the mixture is allowed to stand, centrifuged, washed and dried to obtain a metal-organic framework material;

[0008] The metal-organic framework material is placed in a tubular furnace, heated to 600-1000° C. in an inert protective gas atmosphere, kept warm for 1-4 hours, and naturally cooled to room temperature to obtain a fuel cell catalyst.

[0009] In a possible implementation, the methanol solution of cobalt nitrate, the methanol solution of zinc nitrate and the methanol solution of 2-methylimidazole are mixed, and the mixture is allowed to stand, centrifuged, washed and dried to obtain a metal-organic framework material, comprising:

[0010] The methanol solution of cobalt nitrate and the methanol solution of 2-methylimidazole are mixed and stirred to obtain a mixed solution;

[0011] Adding the zinc nitrate methanol solution to the mixed solution, leaving it to stand for 1 to 12 hours, and centrifuging the product;

[0012] After centrifugation, the product is washed with methanol and dried to obtain the metal-organic framework material.

[0013] In another possible implementation, the methanol solution of cobalt nitrate, the methanol solution of zinc nitrate, and the methanol solution of 2-methylimidazole are mixed in a volume ratio of 1:2:3, 2:1:3, or 1:1:2.

[0014] In another possible implementation, the preparation of the methanol solution of cobalt nitrate, the methanol solution of zinc nitrate and the methanol solution of 2-methylimidazole respectively comprises:

[0015] Add cobalt nitrate hexahydrate into methanol to prepare a 0.1-0.5 mol / L cobalt nitrate methanol solution;

[0016] Add zinc nitrate hexahydrate into methanol to prepare a 0.1-1.0 mol / L zinc nitrate methanol solution;

[0017] 2-Methylimidazole is added to methanol to prepare a 0.5-2.0 mol / L 2-methylimidazole methanol solution.

[0018] In another possible implementation, the concentration of the methanol solution of cobalt nitrate is 0.25 mol / L, the concentration of the methanol solution of zinc nitrate is 0.57 mol / L, and the concentration of the methanol solution of 2-methylimidazole is 1 mol / L.

[0019] In another possible implementation, the inert protective gas includes at least one of nitrogen, argon, hydrogen and argon mixed gas.

[0020] In another possible implementation, the flow rate of the inert protective gas is 10 to 20 L / min, and the heating rate is 1 to 5° C. / min.

[0021] In another possible implementation, the heating temperature is 900° C. and the holding time is 2 h.

[0022] On the other hand, a fuel cell catalyst is provided, wherein the fuel cell catalyst is prepared by any of the preparation methods described above.

[0023] On the other hand, a use of a fuel cell catalyst in preparing a battery electrode material is provided.

[0024] The embodiment of the present application provides a method for preparing a fuel cell catalyst, which is composed of a nitrogen-doped carbon nanocage, cobalt nanoparticles and carbon nanotubes, wherein the carbon nanotubes grow on the surface of the nitrogen-doped carbon nanocage, and the cobalt nanoparticles are coated inside the carbon nanotubes and the carbon nanocage. Among them, the doping of the nitrogen element breaks the chemical reaction inertness caused by the uniform distribution of electrons in the carbon network, increases the catalytic active sites of the catalyst material, and improves the catalytic activity; the Mott-Schottky effect between the cobalt nanoparticles and the carbon material causes the electrons to transfer from the metal material to the carbon material, and this uneven electron distribution further improves the catalytic activity of the catalyst material, and the cobalt nanoparticles are coated inside the carbon material to avoid the problem of poor contact between the active metal nanoparticles and the carbon material. In addition, the carbon nanotubes grown on the surface of the nanocage can increase the specific surface area and graphitization degree of the catalyst material, and the nanocages can be interconnected by forming a three-dimensional network of carbon nanotubes to improve the conductivity of the material, and further improve the catalytic activity of the catalyst material. In addition, the materials used in the catalyst are low in cost and easy to obtain, and the preparation process is simple. Therefore, the catalyst prepared in the present application has both low production cost and high catalytic activity.

[0025] It is to be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a flow chart of a method for preparing a fuel cell catalyst provided in an embodiment of the present application;

[0027] Figure 2 This is a morphology diagram of a catalyst prepared in Example 1 provided in the examples of the present application;

[0028] Figure 3 is a N1s curve diagram of an X-ray photoelectron spectrum of a catalyst prepared in Example 1 provided in an example of the present application;

[0029] Figure 4 This is a morphology diagram of a catalyst prepared in Example 2 provided in the examples of the present application;

[0030] Figure 5 is a Co1s curve diagram of an X-ray photoelectron spectrum of a catalyst prepared in Example 2 provided in an example of the present application;

[0031] Figure 6 This is a morphology diagram of a catalyst prepared in Example 3 provided in the examples of the present application;

[0032] Figure 7 This is a morphology diagram of a catalyst prepared in Example 4 provided in the examples of the present application;

[0033] Figure 8This is a TEM image of a catalyst prepared in Example 4 provided in the examples of the present application;

[0034] Fig. 9 is a HRTEM image of a catalyst prepared in Example 4 provided in the examples of the present application;

[0035] Fig.10 This is an EDS image of a catalyst prepared in Example 4 provided in the examples of the present application;

[0036] Fig.11 is an LSV curve of a catalyst prepared in Examples 1 to 4 provided in the examples of the present application;

[0037] Fig.12 is a CV curve of a catalyst prepared in Examples 1 to 4 provided in the examples of the present application;

[0038] Fig.13 is an LSV curve of a Pt / C catalyst provided in an example of the present application after 10,000 ADTs;

[0039] Fig.14 This is an LSV curve of a catalyst prepared in Example 4 provided in the examples of the present application after 10,000 ADT cycles. DETAILED DESCRIPTION

[0040] In order to make the technical solutions and advantages of the present application clearer, the implementation methods of the present application are described in further detail below.

[0041] On the one hand, the present invention provides a method for preparing a fuel cell catalyst. Figure 1 , the preparation method comprises:

[0042] Step 101: prepare a methanol solution of cobalt nitrate, a methanol solution of zinc nitrate and a methanol solution of 2-methylimidazole respectively.

[0043] Add cobalt nitrate hexahydrate (Co(NO3)2·6H2O) to methanol to prepare a 0.1-0.5 mol / L cobalt nitrate methanol solution;

[0044] Add zinc nitrate hexahydrate (Zn(NO3)2·6H2O) to methanol to prepare a 0.1-1.0 mol / L zinc nitrate methanol solution;

[0045] 2-Methylimidazole is added to methanol to prepare a 0.5-2.0 mol / L 2-methylimidazole methanol solution.

[0046] The concentration of the methanol solution of cobalt nitrate may be 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L. The concentration of the methanol solution of zinc nitrate may be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.57 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L. The concentration of the methanol solution of 2-methylimidazole can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, and 2.0 mol / L.

[0047] Furthermore, the concentration of the methanol solution of cobalt nitrate was 0.25 mol / L, the concentration of the methanol solution of zinc nitrate was 0.57 mol / L, and the concentration of the methanol solution of 2-methylimidazole was 1 mol / L.

[0048] The methanol solution of cobalt nitrate, the methanol solution of zinc nitrate and the methanol solution of 2-methylimidazole are stored at room temperature after preparation.

[0049] In the embodiment of the present application, 2-methylimidazole provides nitrogen and carbon elements, and cobalt nitrate provides cobalt elements. Cobalt nitrate and zinc nitrate coordinate with 2-methylimidazole to generate a metal-organic framework material, and then a subsequent high-temperature carbonization process is performed.

[0050] Step 102: Mix a methanol solution of cobalt nitrate, a methanol solution of zinc nitrate and a methanol solution of 2-methylimidazole, let stand, centrifuge, wash and dry to obtain a metal-organic framework material.

[0051] The methanol solution of cobalt nitrate and the methanol solution of 2-methylimidazole are mixed and stirred evenly to obtain a mixed solution; the methanol solution of zinc nitrate is added to the mixed solution, and the mixture is allowed to stand for 1 to 12 hours, and the product is centrifuged; after centrifugation, the product is washed with methanol and dried to obtain a metal-organic framework material. Among them, the metal-organic framework material can be expressed as ZIF-67@ZIF-8.

[0052] In a possible implementation, a methanol solution of cobalt nitrate, a methanol solution of zinc nitrate, and a methanol solution of 2-methylimidazole are mixed in a volume ratio of 1:2:3, 2:1:3, or 1:1:2.

[0053] Furthermore, a methanol solution of cobalt nitrate, a methanol solution of zinc nitrate, and a methanol solution of 2-methylimidazole are mixed in a volume ratio of 1:1:2.

[0054] The stirring time may be 5 to 20 minutes, for example, the stirring time is 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes. In the embodiments of the present application, only the stirring time of 10 minutes is used as an example for description.

[0055] The standing time can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h. In the embodiment of the present application, only 4h is used as an example for explanation. Just stand at room temperature.

[0056] The number of washing with methanol can be 1 to 5 times, for example, the number of washing is 1, 2, 3, 4, and 5. In the embodiment of the present application, only the number of washing is 3 times as an example for description.

[0057] The temperature during drying can be set and changed as needed. For example, the temperature during drying is 50°C, 60°C, or 70°C. In the embodiment of the present application, only 60°C is used as an example for explanation.

[0058] Step 103: Place the metal-organic framework material into a tubular furnace, heat it to 600-1000° C. in an inert protective gas atmosphere, keep it warm for 1-4 hours, and naturally cool it to room temperature to obtain a fuel cell catalyst.

[0059] The inert protective gas includes at least one of nitrogen, argon, hydrogen and argon mixed gas. For example, the inert protective gas is nitrogen.

[0060] The flow rate of the inert protective gas is 10 to 20 L / min. For example, the flow rate of the inert protective gas is 10 L / min, 12 L / min, 14 L / min, 15 L / min, 16 L / min, 18 L / min, and 20 L / min. In the embodiment of the present application, only the flow rate of the inert protective gas of 15 L / min is used as an example for description.

[0061] The heating rate in the tube furnace is 1-5°C / min, for example, the heating rate is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min. In the embodiment of the present application, only the heating rate of 2°C / min is used as an example for description.

[0062] The heating temperature is 600-1000° C., for example, the heating temperature is 600° C., 650° C., 700° C., 750° C., 800° C., 850° C., 900° C., 950° C., 1000° C. In the embodiment of the present application, only the heating temperature of 900° C. is used as an example for description.

[0063] The heat preservation time is 1 to 4 hours, for example, the heat preservation time is 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours. In the embodiment of the present application, only the heat preservation time of 2 hours is used as an example for description.

[0064] In the embodiment of the present application, the catalyst is composed of nitrogen-doped carbon nanocages, cobalt nanoparticles and carbon nanotubes, carbon nanotubes grow on the surface of nitrogen-doped carbon nanocages, and cobalt nanoparticles are coated inside carbon nanotubes and carbon nanocages. Among them, the diameter of the carbon nanocage is 300-400nm, the diameter of the cobalt nanoparticles is 10-30nm, and the diameter of the carbon nanotubes is 30-50nm. The doping of nitrogen breaks the chemical reaction inertness caused by the uniform distribution of electrons in the carbon network, increases the catalytic active sites of the catalyst material, and improves the catalytic activity; the Mott-Schottky effect between the cobalt nanoparticles and the carbon material causes the electrons to transfer from the metal material to the carbon material. This uneven electron distribution further improves the catalytic activity of the catalyst material, and the cobalt nanoparticles are coated inside the carbon material to avoid the problem of poor contact between the active metal nanoparticles and the carbon material. In addition, the carbon nanotubes grown on the surface of the nanocage can increase the specific surface area and graphitization degree of the catalyst material, and the nanocages can be linked to each other through the three-dimensional network formed by the carbon nanotubes to improve the conductivity of the material and further improve the catalytic activity of the catalyst material. In addition, the materials used in the catalyst are low-cost and easily available, and the preparation process is simple. Therefore, the catalyst prepared in the present application has both low production cost and high catalytic activity.

[0065] On the other hand, a fuel cell catalyst is provided. The fuel cell catalyst is prepared by the above-mentioned preparation method.

[0066] On the other hand, a use of a fuel cell catalyst in preparing a battery electrode material is provided.

[0067] The technical solution of the present application will be described in detail below through specific embodiments.

[0068] In the following specific examples, operations involved without specifying conditions were performed under conventional conditions or conditions recommended by the manufacturer.

[0069] Example 1

[0070] Embodiment 1 provides a catalyst, which is obtained by the following preparation method:

[0071] (1) Preparation of ZIF-8: Add Zn(NO3)2·6H2O to methanol to prepare a 0.57 mol / L Zn(NO3)2·6H2O methanol solution, which is stored at room temperature. Add 2-methylimidazole to methanol to prepare a 1 mol / L 2-methylimidazole methanol solution, which is stored at room temperature. Mix the Zn(NO3)2·6H2O methanol solution and the 2-methylimidazole methanol solution at a volume ratio of 1:1, stir for 10 min, and let stand at room temperature for 4 h. Centrifuge the product, wash with methanol three times, and dry at 60°C to obtain the ZIF-8 material.

[0072] (2) Preparation of nitrogen-doped carbon catalyst: ZIF-8 material was placed in a tubular furnace and heated to 900°C in an inert protective gas nitrogen atmosphere for 2 h at a nitrogen flow rate of 15 L / min and a heating rate of 2°C / min. The catalyst was naturally cooled to room temperature to obtain the catalyst.

[0073] See also Figure 2 , Figure 2 This is a morphology picture of the catalyst prepared in Example 1.

[0074] See also Figure 3 , Figure 3 The N1s curve of the X-ray photoelectron spectrum of the catalyst prepared in Example 1 is shown in FIG. Figure 3 It can be seen that nitrogen elements are successfully doped into carbon materials in the form of nitrogen-containing functional groups such as pyrrolic nitrogen, pyridinic nitrogen, graphitic nitrogen, and oxidized nitrogen.

[0075] Example 2

[0076] Embodiment 2 provides a kind of catalyst, and it is obtained by the following preparation method:

[0077] (1) Preparation of ZIF-67: Add Co(NO3)2·6H2O to methanol to prepare a 0.25 mol / L Co(NO3)2·6H2O methanol solution, which is stored at room temperature. Add 2-methylimidazole to methanol to prepare a 1 mol / L 2-methylimidazole methanol solution, which is stored at room temperature. Mix the Co(NO3)2·6H2O methanol solution and the 2-methylimidazole methanol solution at a volume ratio of 1:1, stir for 10 min, and let stand at room temperature for 4 h. Centrifuge the product, wash with methanol three times, and dry at 60°C to obtain the ZIF-67 material.

[0078] (2) Preparation of nitrogen-doped carbon catalyst loaded with cobalt nanoparticles: The ZIF-67 material was placed in a tubular furnace and heated to 900°C in an inert protective gas nitrogen atmosphere for 2 h at a nitrogen flow rate of 15 L / min and a heating rate of 2°C / min. The catalyst was naturally cooled to room temperature to obtain the catalyst.

[0079] See also Figure 4 , Figure 4 This is a morphology picture of the catalyst prepared in Example 2.

[0080] See also Figure 5 , Figure 5 This is a Co 1s curve of the X-ray photoelectron spectrum of the catalyst prepared in Example 2. The result can prove the existence of cobalt element, indicating that the cobalt nanoparticles are successfully loaded into the carbon material.

[0081] Example 3

[0082] (1) Preparation of ZIF-67@ZIF-8: Add Co(NO3)2·6H2O to methanol to prepare a 0.25 mol / L Co(NO3)2·6H2O methanol solution, which was stored at room temperature. Add Zn(NO3)2·6H2O to methanol to prepare a 0.57 mol / L Zn(NO3)2·6H2O methanol solution, which was stored at room temperature. Add 2-methylimidazole to methanol to prepare a 1 mol / L 2-methylimidazole methanol solution, which was stored at room temperature. Mix the Co(NO3)2·6H2O methanol solution, the Zn(NO3)2·6H2O methanol solution, and the 2-methylimidazole methanol solution at a volume ratio of 1:1:2, stir for 10 min, and let stand at room temperature for 4 h. The product was centrifuged, washed with methanol three times, and dried at 60°C to obtain ZIF-67@ZIF-8 material.

[0083] (2) Preparation of nitrogen-doped catalyst of short carbon nanotube-coated cobalt nanoparticles: The ZIF-67@ZIF-8 material was placed in a tubular furnace and heated to 700°C in an inert protective gas nitrogen atmosphere for 2 h at a nitrogen flow rate of 15 L / min and a heating rate of 2°C / min. The catalyst was naturally cooled to room temperature to obtain the catalyst.

[0084] See also Figure 6 , Figure 6 The morphology of the catalyst prepared in Example 3 is shown in FIG. Figure 6 It can be seen that compared with the catalyst prepared in Example 2, a small amount of short carbon nanotubes are grown in the catalyst prepared in Example 3, and the short carbon nanotubes cover the nitrogen-doped carbon nanomaterial of the cobalt nanoparticles.

[0085] Example 4

[0086] (1) Preparation of ZIF-67@ZIF-8: Add Co(NO3)2·6H2O to methanol to prepare a 0.25 mol / L Co(NO3)2·6H2O methanol solution, which was stored at room temperature. Add Zn(NO3)2·6H2O to methanol to prepare a 0.57 mol / L Zn(NO3)2·6H2O methanol solution, which was stored at room temperature. Add 2-methylimidazole to methanol to prepare a 1 mol / L 2-methylimidazole methanol solution, which was stored at room temperature. Mix the Co(NO3)2·6H2O methanol solution, the Zn(NO3)2·6H2O methanol solution, and the 2-methylimidazole methanol solution at a volume ratio of 1:1:2, stir for 10 min, and let stand at room temperature for 4 h. The product was centrifuged, washed with methanol three times, and dried at 60°C to obtain ZIF-67@ZIF-8 material.

[0087] (2) Preparation of nitrogen-doped catalysts of long carbon nanotubes-coated cobalt nanoparticles: The ZIF-67@ZIF-8 material was placed in a tubular furnace and heated to 900°C in an inert protective gas nitrogen atmosphere for 2 h at a nitrogen flow rate of 15 L / min and a heating rate of 2°C / min. The catalyst was naturally cooled to room temperature to obtain the catalyst.

[0088] See also Figure 7 , Figure 7 The morphology of the catalyst prepared in Example 4 is shown in FIG. Figure 7 It can be seen from both (a) and (b) that compared with the catalyst prepared in Example 3, a large number of long carbon nanotubes are grown in the catalyst prepared in Example 4, and the long carbon nanotubes cover the nitrogen-doped carbon nanomaterial of the cobalt nanoparticles.

[0089] See also Figure 8 , Figure 8 The transmission electron microscope (TEM) image of the catalyst prepared in Example 4, wherein: Figure 8 The 12nm, 13nm, and 14nm shown in (a) are the diameters of cobalt nanoparticles. Figure 8 The 34 nm, 38 nm, 43 nm, 45 nm, and 48 nm shown in (b) are all the diameters of carbon nanotubes.

[0090] See also Fig. 9 , Fig. 9 This is a high resolution transmission electron microscopy (HRTEM) image of the catalyst prepared in Example 4. Fig. 9 The middle framed part of (a) is the cobalt nanoparticle, and the part indicated by the arrow is the carbon wall of the carbon nanotube. Fig. 9 (b) for Fig. 9 (a) The enlarged display of the boxed part Fig. 9 (b) shows that the lattice spacing d of cobalt 111= 0.21nm, the lattice spacing d of carbon 002 =0.34nm. And from Fig. 9 It can be seen in (b) that the carbon is on the outside of the cobalt, which also shows that the catalyst prepared in Example 4 is indeed carbon nanotube-coated cobalt nanoparticles.

[0091] See also Fig.10 , Fig.10 This is an energy dispersive X-ray spectroscopy (EDS) diagram of the catalyst prepared in Example 4. Fig.10 (a) is a schematic diagram of the distribution of elements on the catalyst surface. Fig.10 (b) is a schematic diagram of the distribution of carbon elements in the catalyst. Fig.10 (c) is a schematic diagram of the distribution of nitrogen in the catalyst. Fig.10 (d) Schematic diagram of the distribution of cobalt element in the catalyst.

[0092] Combination Figures 7 to 10 , it can be shown that Example 4 successfully prepared the nitrogen-doped carbon catalyst of carbon nanotube-coated cobalt nanoparticles.

[0093] It should be noted that the catalyst prepared by carbonization of ZIF-8 synthesized by adding zinc nitrate and 2-methylimidazole in Example 1 did not grow carbon nanotubes, which was due to the lack of catalyst cobalt. The catalyst prepared by carbonization of ZIF-67 synthesized by adding cobalt nitrate and 2-methylimidazole in Example 2 resulted in insufficient carbon source required for carbon nanotube growth due to the lack of ZIF-8 coating, so no carbon nanotubes were grown in the catalyst. While Example 3 and Example 4 simultaneously added cobalt nitrate, zinc nitrate and 2-methylimidazole to synthesize ZIF-67@ZIF-8, ZIF-67 provided catalyst cobalt for carbon nanotube growth, and ZIF-8 provided sufficient carbon source, so carbon nanotubes were grown in the catalyst. It can be seen that the necessary condition for growing carbon nanotubes is a nanomaterial with a ZIF-8 shell providing sufficient carbon source and a ZIF-67 core providing catalyst cobalt.

[0094] In addition, although carbon nanotubes were grown in Example 3, the grown carbon nanotubes were short and in small quantity. This was because the heating temperature (700°C) in Example 3 was relatively low, while the heating temperature (900°C) in Example 4 was relatively high and suitable for the growth of carbon nanotubes. Therefore, the grown carbon nanotubes were long and in large quantity.

[0095] Application Examples

[0096] All ORR tests in this experiment were performed on a Shanghai Chenhua Instruments CHI760e electrochemical workstation. A three-electrode test system was used, with a glassy carbon electrode as the working electrode and a 1 cm 2The platinum sheet was used as the counter electrode, mercury / mercury oxide (Hg / HgO) was used as the reference electrode, and 0.1 mol / L KOH was used as the electrolyte. All electrochemical tests were performed in a 25°C constant temperature water bath.

[0097] Preparation of slurry: 5 mg of the ground catalyst was accurately weighed and evenly dispersed in a mixed solution consisting of 995 μL of ethanol and 5 μL of Nafion. The mixed solution was then placed in an ultrasonic machine and ultrasonicated for 1 hour to make the catalyst evenly dispersed. This evenly dispersed catalyst was used to prepare the working electrode.

[0098] To explore the activity of the catalyst in ORR, linear sweep voltammetry (LSV) was used for testing. LSV testing was performed in an O2-saturated KOH electrolyte with a scan rate of 20 mV·s -1 , the scanning voltage range was -0.9 to 0.3 V, and the rotation speed of the ring-disk electrode was 1600 rpm.

[0099] The CV curve (O2) test conditions of the catalyst are: in 0.1 mol / L KOH electrolyte, at a set voltage range of -0.9 to 0.3 V and 50 mV·s -1 Cyclic voltammetry (CV) was performed at a scan rate of 100 % until a stable curve was obtained.

[0100] In order to evaluate the stability of the obtained catalyst, the half-wave potential difference in the LSV curve of the catalyst material before and after the accelerated durability test (ADT) was compared. This experiment was carried out in an environment of 0.1 mol / L KOH electrolyte. We continuously introduced O2 and -1 The catalyst sample was subjected to 10000 cycles of CV test at a scan rate of .

[0101] like Fig.11 As shown, the O2 saturated system is 1600rpm and 10mV·s -1 The LSV curves below show the half-wave potential (E 1 / 2 ), it can be seen that the catalyst prepared in Example 4 exhibits a higher half-wave potential, namely E 1 / 2 It is 0.78V (vs RHE), indicating that it has good performance.

[0102] like Fig.12 As shown in the CV curve under O2 saturation state, the catalyst prepared in Example 4 exhibits stronger oxygen reduction activity than the catalysts prepared in Examples 1 to 3.

[0103] In order to verify the durability of the catalyst prepared in Example 4, an accelerated durability test (ADT) was used for evaluation. Fig.13 and Fig.14 As shown, the half-wave potential of the Pt / C catalyst decreased by 32 mV, while the half-wave potential of the catalyst prepared in Example 4 decreased by only 20 mV. This shows that the catalyst prepared in Example 4 has higher durability.

[0104] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a fuel cell catalyst, characterized in that: The preparation method comprises: respectively preparing a methanol solution of cobalt nitrate, a methanol solution of zinc nitrate and a methanol solution of 2-methylimidazole; The cobalt nitrate methanol solution, the zinc nitrate methanol solution and the 2-methylimidazole methanol solution are mixed, and the mixture is allowed to stand, centrifuged, washed and dried to obtain a metal-organic framework material; The metal-organic framework material is placed in a tubular furnace, heated to 600-1000° C. in an inert protective gas atmosphere, kept warm for 1-4 hours, and naturally cooled to room temperature to obtain a fuel cell catalyst.

2. The preparation method according to claim 1, characterized in that: The method comprises mixing the methanol solution of cobalt nitrate, the methanol solution of zinc nitrate and the methanol solution of 2-methylimidazole, standing, centrifuging, washing and drying to obtain a metal-organic framework material, comprising: The methanol solution of cobalt nitrate and the methanol solution of 2-methylimidazole are mixed and stirred to obtain a mixed solution; Adding the zinc nitrate methanol solution to the mixed solution, leaving it to stand for 1 to 12 hours, and centrifuging the product; After centrifugation, the product is washed with methanol and dried to obtain the metal-organic framework material.

3. The preparation method according to claim 1 or 2, characterized in that: The methanol solution of cobalt nitrate, the methanol solution of zinc nitrate, and the methanol solution of 2-methylimidazole are mixed in a volume ratio of 1:2:3, 2:1:3, or 1:1:

2.

4. The preparation method according to claim 1, characterized in that: The method of separately preparing a methanol solution of cobalt nitrate, a methanol solution of zinc nitrate and a methanol solution of 2-methylimidazole comprises: Add cobalt nitrate hexahydrate into methanol to prepare a 0.1-0.5 mol / L cobalt nitrate methanol solution; Add zinc nitrate hexahydrate into methanol to prepare a 0.1-1.0 mol / L zinc nitrate methanol solution; 2-Methylimidazole is added to methanol to prepare a 0.5-2.0 mol / L 2-methylimidazole methanol solution.

5. The preparation method according to claim 1, characterized in that: The concentration of the methanol solution of cobalt nitrate is 0.25 mol / L, the concentration of the methanol solution of zinc nitrate is 0.57 mol / L, and the concentration of the methanol solution of 2-methylimidazole is 1 mol / L.

6. The preparation method according to claim 1, characterized in that: The inert protective gas includes at least one of nitrogen, argon, hydrogen and argon mixed gas.

7. The preparation method according to claim 1, characterized in that: The flow rate of the inert protective gas is 10 to 20 L / min, and the heating rate is 1 to 5° C. / min.

8. The preparation method according to claim 1, characterized in that: The heating temperature is 900°C and the holding time is 2h.

9. A fuel cell catalyst, characterized in that: The fuel cell catalyst is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the fuel cell catalyst according to claim 9 in the preparation of battery electrode materials.

Citation Information

Patent Citations

  • Cobalt monatomic loaded nitrogen-doped carbon oxygen reduction catalyst and preparation method thereof

    CN111468167A

  • Preparation method of cobalt-nitrogen co-doped carbon nanocage

    CN112678802A

  • Oxygen reduction electrocatalyst of cobalt monatomic isolated platinum nanoparticles and preparation method of oxygen reduction electrocatalyst

    CN115318322A

  • Preparation method and application of ZIF-67-ZIF-8 cobalt-based catalyst with core-shell structure

    CN116586093A

  • Carbon tube grafted nitrogen-doped carbon-supported iron / cobalt-based catalyst applied to zinc-air battery and preparation method of carbon tube grafted nitrogen-doped carbon-supported iron / cobalt-based catalyst

    CN118136865A